Strategic integration of social capital and good governanceof the local governments for sustainability In Khwao Sinarin District, Surin Province - Charoaytao, Chuleeporn (Journal of Local Governance and Innovation, 2019)
This research aims to study the social capital of a local government in Khwao Sinarin District, Surin Province and to propose the creation of a strategic integration of social capital and governance of the organization that contribute to sustainable development in the district. This research used the quantitative research studies. The data were collected from residents in Khwao Sinarin District, Surin province of 395 cases with multi-stage random sampling method. A questionnaire was prepared as a tool to collect data. The data were analyzed by percentage, average and standard deviation. The results showed that the strategic integration of social capital and governance of local governments for sustainability in Khwao Sinarin District, Surin province was overall at average level. Considering each aspect, it was found that on an average the most was the knowledge management, infrastructure, moral, responsibility, value, social venture including good governance, the transparency of the income, trust, the rule of law, participation, respectively, and the average minimum is the personnel. All of those have high average level.